Plate and K-wire show advantages to nailing for distal diametaphyseal radius fracture in children: a retrospective, two-center study - Weil, Frederik; Fabarius, Lucas; Weil, Luisa; Grützner, Paul Alfred; Boettcher, Michael; Weiß, Christel; Studier-Fischer, Stefan (Journal of Clinical Medicine, 2025)
Background/Objectives: Distal forearm fractures are the most common fractures in children. Three surgical techniques are most commonly used at the level of the radial diametaphysis on the distal forearm in children: K-wire, ascending ESIN (elastic stable intramedullary nail) or plate osteosynthesis. The aim of this study was to compare these procedures in children with distal diametaphyseal radius fractures regarding operative and functional outcome. Methods: A retrospective study was conducted in two level 1 trauma centers. Children and adolescents aged 2 to 15 years were included. The study period was from January 2010 to December 2022. The hospital information system was used to record patient age, gender, height, weight, fracture location, degree of angular deformity postoperatively, surgical procedure and postoperative complications, which were described in the medical records of the hospital information system. Complications graded by modified Clavien-Dindo-Sink served as the primary outcome. Reduction accuracy, operative and fluoroscopy times, immobilization length and postoperative motion were the secondary endpoints. Results: A total of 213 children were included in the study. K-wire osteosynthesis was performed in 25%, nailing in 19% and volar plate osteosynthesis in 55%. All ESIN were inserted in ascending technique. Complications occurred in 22% of patients and did not differ overall between techniques (p = 0.20). Severe complications were significantly more frequent after ESIN (20%) than after K-wires (7%) or plates (4%) (p = 0.04). Plate fixation achieved the most accurate alignment (≤5° angular deformity in 93% vs. 57% K-wires and 61% ESIN; p < 0.0001) and the fewest late motion restrictions (p = 0.02). K-wire surgery was fastest technique and required the least fluoroscopy, but necessitated the longest postoperative cast. Conclusions: Volar plating combines reliable anatomical reduction with a low rate of major complications and early mobilization, supporting its use in older children whose remodeling potential is limited. K-wires are a swift, minimally invasive option for younger patients, albeit with less precise reduction and prolonged immobilization. Conventional ESIN showed the highest burden of severe complications.
Gesehen am 10.09.2025